2019
DOI: 10.1101/788323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Networks and Key Regulators of the Dysregulated Neuronal System in Alzheimer’s Disease

Abstract: To study the molecular mechanisms driving the pathogenesis and identify novel therapeutic targets of late onset Alzheimer's Disease (LOAD), we performed an integrative network analysis of whole-genome DNA and RNA sequencing profiling of four cortical areas, including the parahippocampal gyrus, across 364 donors spanning the full spectrum of LOAD-related cognitive and neuropathological disease severities. Our analyses revealed thousands of molecular changes and uncovered for the first-time multiple neuron speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
4
10
0
Order By: Relevance
“…Previous work has shown that the hippocampus is strongly associated with A and tau accumulation and early memory loss in AD (24). We have also shown in previous studies of the MSBB-AD cohort that transcriptomic changes in the PHG region highly overlap the Kyoto Encyclopedia of Genes and Genomes (KEGG) (25) Alzheimer's and Parkinson's disease gene sets and are correlated with high A plaque density (19), demonstrating that these changes are consistent with AD disease progression. Therefore, the PHG region carries the strongest molecular signature of AD.…”
Section: The Phg Carries the Strongest Molecular Signal Of Loadsupporting
confidence: 79%
See 3 more Smart Citations
“…Previous work has shown that the hippocampus is strongly associated with A and tau accumulation and early memory loss in AD (24). We have also shown in previous studies of the MSBB-AD cohort that transcriptomic changes in the PHG region highly overlap the Kyoto Encyclopedia of Genes and Genomes (KEGG) (25) Alzheimer's and Parkinson's disease gene sets and are correlated with high A plaque density (19), demonstrating that these changes are consistent with AD disease progression. Therefore, the PHG region carries the strongest molecular signature of AD.…”
Section: The Phg Carries the Strongest Molecular Signal Of Loadsupporting
confidence: 79%
“…For example, many protein degradationrelated genes, including ubiquitination and polyubiquitination, protein catabolism, the proteasome, and proteins targeting for destruction, are up-regulated in subtype A while organic acid-related genes, including acid secretion and acidic amino acid transport, are specifically on January 10, 2021 http://advances.sciencemag.org/ Downloaded from up-regulated in class B. Defects in the acidification of lysosomes in neurons have been previously associated with neuronal and synaptic loss in AD, as well as decreases in long-term potentiation (19).…”
Section: Molecular Signatures Of Putative Ad Subtypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides synaptic and neuronal loss, AD pathology is also accompanied by changes in astrocytic and microglial cells, and human genome-wide association studies (GWASs) support a causal role for immune mechanisms ( Jansen et al, 2019 ; Kunkle et al, 2019 ; Raj et al, 2014 ). Results from RNA sequencing (RNA-seq) of human postmortem brain tissue further reinforce the importance of microglial and inflammatory mechanisms in AD pathogenesis, among other pathways ( Allen et al, 2018 ; Conway et al, 2018 ; McKenzie et al, 2017 ; Patrick et al, 2017 ; Wang et al, 2016 , 2019 ; Zhang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 86%